Detection of pathogenic leptospira in environmental sources from selected urban sites and national park in Sarawak - Choe, Sin Pei. (Universiti Malaysia Sarawak (UNIMAS), 2015)
Leptospirosis which is caused by pathogenic Leptospira had been gazetted as one of the notifiable zoonotic diseases in Malaysia since year 2010. According to the reports by Sarawak State Health Department, based on the cases in 2014, the drastic increase of leptospirosis cases happened in Sarawak had reached 616 cases with 24 deaths. Several recent studies have reported the isolation of pathogenic Leptospira from environmental soil and water in recreational parks and selected national service training centres in Malaysia. However, there is very limited information about this disease in water and soils of urban sites, particularly in Sarawak. Thus, this project was carried out to study the occurrence of pathogenic Leptospira in environmental sources (water and soil) from urban areas and national park in Kuching, Sarawak. A total of 360 samples (180 soil and 180 water) were collected from Gunung Gading National Park (GGNP) and the residential and commercial area of six urban areas in Kuching. The samples were processed through ultrapore membrane filtration and then inoculated into EMJH medium followed by the incubation period of 30 days. PCR was conducted to detect pathogenic Leptospira by using lipL32-270FllipL32-692R primers which target on /ipL32 genes. There were 5.6% (20/360) of environmental sources tested positive for pathogenic Leptospira. In comparison, detectable leptospital DNA was presented in 0.83% (11120) environmental sources from national park and 7.9% (19/240) environmental sources from six urban areas. The result demonstrated high prevalence of Leptopira in the environmental sources from urban areas than that from national park. Additionally, Leptospira presented higher prevalence in soil samples (10%) than that in water samples (1.1 %). Further identification of isolates in strain and serovar level is needed to understand the distribution of Leptospira in urban sites of Kuching to prevent leptospirosis outbreak.